Mexican cuisine spaces at the beginning of the 20th century. The alchemical creation of smells, tastes and textures - Arana López, Gladys Noemí; Universidad Autónoma de Yucatán (Instituto Carlos Arbeláez Camacho para el patrimonio arquitectónico y urbano, 2014)
The main objective of this paper, was the comprehensive understanding of the kitchen as the living space wheremultiple cultural practices are amalgamated, where the intangible becomes matter and where the material becomesdisembodied. The study universe was formed by those located in the houses of the Mexican elite during the years1886-1916 and was analyzed with the tooling used for the study of everyday life in conjunction with those used in theanalysis of architectural space, being used many diverse sources of information such as plans, manuals of etiquetteand recipes. This analysis provides a look of the insight of the phenomenon of spatial compartmentalization, functionalspecialization and the relationship between material and symbolic idealization, expressed as a whole as the substantialbase of modern functionality in this region of Mexico. The continuity of this work presents many opportunities aswe can study the space itself deeper, their permanence, transformation, construction techniques, evolution of hometechnology and family dynamics, among many other possibilities: